Analysis of Community Satisfaction with the Use of Electric Motorbikes in the City of South Surabaya - Narendra, Ravaelino Dimas Eka; Irawati, Desrina Yusi (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Mode of transportation is one of the basic human needs in carrying out an activity. Transportation consists of land, sea and air transportation. The development of modern transportation can be viewed from several aspects, such as quality, effectiveness and efficiency for its users, especially the millennial generation. One of the modern transportation today is an electric motorcycle. The development of electric motorcycles in Indonesia is not as fast as the development of conventional motorcycles. Electric motorcycles that are currently developing need to be analyzed to determine the level of consumer satisfaction. Analysis of the level of customer satisfaction can be done using the method. By knowing the analysis of the Kano method, improvements or evaluations can be made for developers of relevant electric motors in the future. Test analysis was carried out by conducting a survey of electric motorcycle users in the Surabaya area. Based on the analysis of the results of Kano's research that has been done, it can be seen that there is a need for an increase in electric motorbikes. This shows that with an increase in electric motorbikes, people's satisfaction with the use of electric motorbikes will increase.